Effect of palm oil clinker (POC) aggregates on fresh and hardened properties of concrete - Abutaha, F.; Razak, H.A.; Kanadasan, Jegathish (Elsevier, 2016)
Utilizing waste material in the construction industry is an effective way to protect the environment and minimize construction cost. In this paper, palm oil clinker (POC) aggregates were used as coarse and fine aggregate replacement in lightweight concrete production. This study focused mainly on investigating the effect of both partial and full replacement of the aggregates with POC on the physical and mechanical properties of concrete. Department of Environment (DOE) method was adopted for the mix design to produce concrete Grade 40. The approach used in the mix design involved POC replacement of 0%, 10%, 20%, 40%, 60%, 80%, and 100% of the total volume of fine and coarse aggregates. The parameters investigated in this study include the slump and density for the fresh properties, as well as the compressive strength and ultrasonic pulse value (UPV) tests at 3, 7, 14, and 28 days for the hardened properties. The hardened density at 28 days was within the range of 2074–2358 kg/m3. Test results showed that POC exhibited good UPV value and an acceptable compressive strength of 33–49 MPa at 28 days. Thus, POC has a good potential to replace natural aggregates, making it suitable to be used in concrete.